Consumer Choice Behavior in Partnership Systems (Teseng): Qualitative Analysis of Theory of Planned Behavior - Kara, Muslimin; Rusanti, Ega; Sofyan, A. Syathir (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The increase in research on local economic practices is not accompanied by theoretical analysis. This study explores people's behaviour in choosing partnership systems (Teseng) by analyzing the theory of planned behaviour. Therefore, this research implies that it is an instrument for measuring local economic practices from the perspective of the theory of planned behaviour. The methodology used was phenomenology with data from the Batukaropa village community, Bulukumba Regency, Indonesia. The results show that attitude toward a behaviour is indicated by a perspective of helping and strengthening kinship. Meanwhile, subjective norms consist of the perception that teseng is part of the social culture of society, and the practice of teseng reflects social status. Perceived behaviour control based on the practice of teseng is more flexible and effective than the procedures for applying venture capital in Islamic banking.